A Survey on Privacy Preserve Methods in Data Aggregation - Harsha , K.M; James, Divya (International Journal of Computer Sciences and Engineering, 2019)
Wireless Sensor network has improved their enhancement in enormous applications like monitoring environment, health application monitoring, military surveillance and also tracking of target that are of real time field. When there is communication between the nodes it affects the network lifetime which results in large consumption of energy. In order to reduce this energy consumption, Data aggregation techniques have been employed which eliminates the unnecessary data that is travelling from source node to sink node. When Wireless Sensor Network is deployed in a hostile environment the sensor node would be susceptible to node failures and also compromised by the adversary, thus it would become critical. There are different data aggregation approaches in wireless sensor network mainly used to increase the consumption of energy and also there are different approaches to preserve the data aggregation mainly used protect the data. It also preserves the various security issues such as data freshness, data integrity, data confidentiality in data aggregation.